Water-food-energy-environment synergies and tradeoffs: major issues and case studies - McCornick, Peter G.; Awulachew, Seleshi Bekele; Abebe, M. (IWA Publishing, 2008)
The already complex interrelationships between water, food, energy and the environment are facing both challenges and opportunities. Rising fuel costs and increasing concerns over the effects of climate change are reinvigorating policymakers’ interest in renewable energy sources such as hydropower and bio-energy—both from biofuels as well as biomass. Development of any of these sources has the potential to generate positive economic and environmental benefits, yet, at the same time, they can cause negative food and equity impacts. This obviously entails major tradeoffs between the food, energy and environmental goals of water and energy development, allocation and management. Using both a brief global overview as well as a closer review of four case studies from India, Ethiopia, Jordon and the USA, this paper tries to (i) a present the nature of the tradeoffs under different hydrological, energy, agricultural and environmental contexts and (ii) provide some anecdotal evidence and illustrative cases for the available policy options for minimizing conflicts but maximizing synergies between water, energy, food and environment.